Temporary Autonomous Research : Falke Pisano, Jeremiah Day, Nicoline van Harskamp - Slager, Henk; Shanghai Biennale Shanghai 2012; Marchart, Oliver (Utrecht : Metropolis M Books, 2012)
Pisano, Falke ; Day, Jeremiah ; van Harskamp, Nicoline
Amsterdam Pavilion, 9th Shanghai Biennale
kunstcatalogus